If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 48 + -3x = 6x + 17 Reorder the terms: 48 + -3x = 17 + 6x Solving 48 + -3x = 17 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 48 + -3x + -6x = 17 + 6x + -6x Combine like terms: -3x + -6x = -9x 48 + -9x = 17 + 6x + -6x Combine like terms: 6x + -6x = 0 48 + -9x = 17 + 0 48 + -9x = 17 Add '-48' to each side of the equation. 48 + -48 + -9x = 17 + -48 Combine like terms: 48 + -48 = 0 0 + -9x = 17 + -48 -9x = 17 + -48 Combine like terms: 17 + -48 = -31 -9x = -31 Divide each side by '-9'. x = 3.444444444 Simplifying x = 3.444444444
| (k+2)2w^2+4w+6=0 | | 193-6x=6x+30 | | 5*x+16*y=789 | | 6x-3=15x | | 2(i-3)=14 | | 6p=3p+30 | | 2g-3=1 | | 6x-4=3x+10 | | 3x+5-(2x+1-(2x-3-(x-2)))=x+15 | | 106-5x=22+22 | | 3u^2=11u+4 | | 4a+8=6(a+4) | | 17x+4y=67 | | 30-3x=6-3x | | 3a+4b=12 | | 3x-3v=3t | | x^2+14x=4 | | .5x=12+2x | | 6x+10=78x+x | | -17+-10*x=10+23 | | 10x-11=8+3 | | X^2-8X=17 | | 7x=24+39 | | 58-6x=3x+17 | | 3x^2y-9xy-12y= | | (x-1)(x+2)=(2x-3)(x+4) | | p/100=21/63 | | 12x+19=5x+117 | | 144-7x=20x+18 | | 5y+20=3(y-3) | | 1.7d=3.74 | | -(-8y-6z-1)= |